Remote severity assessment in atopic dermatitis: Validity and reliability of the remote Eczema Area and Severity Index and Self-Administered Eczema Area and Severity IndexCapsule Summary - Aviël Ragamin, MD; Renske Schappin, PhD; N. Tan Nguyen, MD; Anouk E.M. Nouwen, MD; Lisanne F. Hoekstra, MD; Marie L.A. Schuttelaar, MD, PhD; Suzanne G.M.A. Pasmans, MD, PhD (Elsevier, 2023)
Background: Reliable assessment of atopic dermatitis (AD) severity is necessary for clinical practice and research. Valid and reliable remote assessment is essential to facilitate remote care and research. Objectives: Assess the validity and reliability of the Eczema Area and Severity Index (EASI) based on images and patient-assessed severity based on the Self-Administered EASI (SA-EASI). Methods: Whole-body clinical images were taken during consultation from children with AD. After consultations, caregivers completed the SA-EASI and provided images from home. Four raters assessed all images twice using EASI. Results: A total of 1534 clinical images and 425 patient-provided images were collected from 87 and 32 children. Excellent (0.90) validity, good inter (0.77) and intrarater reliability (0.91), and standard error of measurement (4.31) was found for the EASI based on clinical images. Feasibility of patient-provided images showed limitations with missing images (43.8%) and quality issues (23.1%). However, good validity (0.86), inter (0.74) and intrarater reliability (0.94) were found when assessment was possible. Moderate correlation (0.60) between SA-EASI and EASI was found. Limitations: Low portion patient-provided images. Conclusion: AD severity assessment based on images strongly correlates with in-person AD assessment. Good measurement properties confirm the potential of remote assessment. Moderate correlation between SA-EASI and in-person EASI suggest limited value of self-assessment.